Passionate Centrism : One Rabbi's Judaism. - Fine, David J. (Rowman & Littlefield Publishers, 2016)
Passionate Centrism is an important discussion of Positive Historical Judaism and the benefit of holding the center of Judaism-that is, the Conservative Movement. This book is an important resource for clergy and other congregational leaders and is an excellent product for lecture series.